Nucleocytoplasmic Transport of RNAs and RNA–Protein Complexes. Issue 10 (22nd May 2016) - Sloan, Katherine E.; Gleizes, Pierre-Emmanuel; Bohnsack, Markus T.
Abstract: RNAs and ribonucleoprotein complexes (RNPs) play key roles in mediating and regulating gene expression. In eukaryotes, most RNAs are transcribed, processed and assembled with proteins in the nucleus and then either function in the cytoplasm or also undergo a cytoplasmic phase in their biogenesis. This compartmentalization ensures that sequential steps in gene expression and RNP production are performed in the correct order and it allows important quality control mechanisms that prevent the involvement of aberrant RNAs/RNPs in these cellular pathways. The selective exchange of RNAs/RNPs between the nucleus and cytoplasm is enabled by nuclear pore complexes, which function as gateways between these compartments. RNA/RNP transport is facilitated by a range of nuclear transport receptors and adaptors, which are specifically recruited to their cargos and mediate interactions with nucleoporins to allow directional translocation through nuclear pore complexes. While some transport factors are only responsible for the export/import of a certain class of RNA/RNP, others are multifunctional and, in the case of large RNPs, several export factors appear to work together to bring about export. Recent structural studies have revealed aspects of the mechanisms employed by transport receptors to enable specific cargo recognition, and genome-wide approaches have provided the first insights into the diverse composition of pre-mRNPs during export. Furthermore, the regulation of RNA/RNP export is emerging as an important means to modulate gene expression under stress conditions and in disease. Graphical abstract: Highlights: General principles of RNA/RNP transport pathways. Recent insights into the mechanisms of RNA/RNP nucleocytoplasmic transport. tRNAs and snRNAs undergo several passages through nuclear pore complexes. Pre-ribosomal subunits require multiple transport factors for their nuclear export. Nuclear export pathways for mRNAs, miRNA precursors and other RNA species.